The Impact of Overstocking and Negative Energy Balance on Quantitative Measurement of Non-typhoidal Salmonella in Periparturient Dairy Cattle - Muñoz-Vargas, Lohendy; Pempek, Jessica A.; Proudfoot, Kathryn; Eastridge, Maurice L.; Rajala-Schultz, Päivi J.; Wittum, Thomas; Habing, Gregory (Frontiers in Veterinary Science, 2022)
Stressful conditions in animal production facilities may exacerbate the fecal shedding and foodborne transmission of non-typhoidal Salmonella enterica subsp. enterica. Dairy cows are reservoirs of this zoonotic microorganism, and its prevalence has roughly doubled in the past decade on dairy farms in United States. Dairy cows are commonly overstocked at the feed bunk, and stressors placed on the animal prior to parturition may exacerbate Salmonella shedding. However, no studies have evaluated the impact of overstocking and metabolic stress on fecal concentrations of the pathogen. Therefore, we conducted a field trial with 120 multiparous dairy cows randomized into one of four treatment groups with different stocking densities at the feed bunk during the periparturient period as follows: US, understocked from -60 to -1 DRC; OS, overstocked from -60 to -1 DRC; USOS, understocked from -60 to -26 DRC/ overstocked from -25 to -1 DRC; and OSUS, overstocked from -60 to -26 DRC/ understocked from -25 to -1 DRC. Fecal and blood samples were collected at four time points relative to calving. qPCR assays were used to quantify Salmonella invA gene and total bacterial community from fecal samples, and a subset of isolates recovered from fecal bacterial culture were characterized using pulsed field gel electrophoresis and serotyping. Serum non-esterified fatty acids (NEFA) were measured as a metabolic stress indicator using an immunoassay. Multivariable analyses were performed to test if changes in Salmonella concentrations were associated with stocking density, energy balance, or days relative to calving. From fecal isolates, three Salmonella serovars were identified, S. Cerro; Kentucky; Meleagridis. Concentrations of Salmonella increased as cows approached calving. Higher stocking densities at the feed bunk did not impact total bacterial community or NEFA; however, cows in the overstocked groups had higher Salmonella fecal concentrations. Further, cows with higher NEFA concentrations after calving had a higher likelihood of detection of Salmonella. Future farm interventions should aim to reduce environmental and metabolic stress during the periparturient period to decrease the dissemination of Salmonella to cattle, the environment, and humans.